2022
DOI: 10.48550/arxiv.2201.08845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Point-NeRF: Point-based Neural Radiance Fields

Abstract: Figure 1. Point-NeRF uses neural 3D points to efficiently represent and render a continuous radiance volume. The point-based radiance field can be predicted via network forward inference from multi-view images. It can then be optimized per scene to achieve reconstruction quality that surpasses NeRF [35] in tens of minutes. Point-NeRF can also leverage off-the-shelf reconstruction methods like COLMAP [44]and is able to perform point pruning and growing that automatically fix the holes and outliers that are comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As a representative work, NeRF [15] pushes the neural scene representation to a new high level [27,28]. Related works based on the NeRF, including NeRF in the wild [29], NeRF body [30], and Point-NeRF [31], Human-NeRF [32], extend the NeRF to various applications. A comprehensive review of neural rendering has been reported in [33].…”
Section: Learning-based Methodsmentioning
confidence: 99%
“…As a representative work, NeRF [15] pushes the neural scene representation to a new high level [27,28]. Related works based on the NeRF, including NeRF in the wild [29], NeRF body [30], and Point-NeRF [31], Human-NeRF [32], extend the NeRF to various applications. A comprehensive review of neural rendering has been reported in [33].…”
Section: Learning-based Methodsmentioning
confidence: 99%
“…This hybrid representation enables direct manipulation of the object geometry by editing the point cloud or the mesh extracted from our representation for fine-grained rigid or non-rigid body transformation. Unlike prior work Xu et al (2022), SPIDR estimates SDF which is critical to (i) extract higher quality meshes and surfaces for deformation and (ii) obtain better light visibility and surface normals for scene illumination.…”
Section: Geometry Editingmentioning
confidence: 99%
“…For the pure implicit method, rendering the final color of each pixel requires hundreds of network queries, making it hard to complete the computation in a short time. Some methods [Lombardi et al 2021;Xu et al 2022;Yu et al 2021a] exploit the sparse features of other representations such as mesh-based and primitive-based representations to improve efficiency. Other methods try to reduce the querying time and count.…”
Section: Related Work 21 Neural Radiance Field and Important Variantsmentioning
confidence: 99%